Shoulder and hip roll differences between breathing and non-breathing conditions in front crawl swimming - Psycharakis, S. G.; McCabe, C. (Journal of Biomechanics, 2011)
The effects of breathing on body roll have been previously investigated for the roll of the whole trunk only. The purposes of this study were: to calculate separately the shoulder roll (SR) and hip roll (HR) of swimmers during front crawl for non-breathing and preferred-side breathing conditions; to assess the differences in the magnitude and temporal characteristics of these variables between non-breathing and preferred-side breathing conditions; and to examine their association with swimming performance (indicated by swimming speed). Twelve male swimmers who competed at national and international level performed two maximum 25 m front crawl trials: one non-breathing and one with breathing to their preferred side. Performance was recorded with four below and two above water synchronised cameras. SR and HR in both trials were calculated for the breathing and non-breathing sides. The timings of SR and HR peaks to each side and at the positions of neutral roll were also calculated. Swimming speed was significantly slower in the breathing trial (p<0.01). Swimmers rolled their shoulders and hips to the breathing side significantly more in the breathing than in the non-breathing trial (SR: p<0.01; HR: p=0.03). Nevertheless, there were no significant differences in the overall SR or HR between these trials. In the breathing trial, SR was higher in the breathing than in the non-breathing side (p<0.01) but HR was not significantly different (p=0.07). There was no evidence to suggest that temporal characteristics of SR or HR were associated with swimming performance